Volumetric Measurement of Optic Nerve Head Drusen Using Swept-Source Optical Coherence Tomography. Issue 9 (September 2017) - Tsikata, Edem; Vercellin Verticchio, Alice C.; Falkenstein, Iryna; Poon, Linda Yi-Chieh; Brauner, Stacey; Khoueir, Ziad; Miller, John B.; Chen, Teresa C.
Abstract : Purpose: To describe new software tools for quantifying optic nerve head drusen volume using 3-dimensional (3D) swept-source optical coherence tomography (SS-OCT) volumetric scans. Materials and Methods: SS-OCT was used to acquire raster volume scans of 8 eyes of 4 patients with bilateral optic nerve head drusen. The scans were manually segmented by 3 graders to identify the drusen borders, and thereafter total drusen volumes were calculated. Linear regression was performed to study the relationships between drusen volume, retinal nerve fiber layer thickness, and Humphrey visual field mean deviation. Results: In the 8 study eyes, drusen volumes ranged between 0.24 to 1.05 mm 3 . Visual field mean deviation decreased by ∼20 dB per cubic millimeter increase in drusen volume, and the coefficient of correlation of the linear regression was 0.92. In this small patient series, visual field defects were detected when drusen volume was larger than about 0.2 mm 3 . Conclusions: Software tools have been developed to quantify the size of OHND using SS-OCT volume scans.